Pengalaman Subjektif Kualitas Hidup Orang Tua Tunggal Berstatus Cerai - Nafi'ul Tazhkiroh; Eny Purwandari; Taufik (Fakultas of Psychology, Universitas Muria Kudus, 2025)
Single parenthood is a situation where only the father or mother is solely responsible for the family's well-being after a divorce. The change from a couple to a single parent often has psychological impacts that, if not properly managed, can reduce quality of life. Quality of life is understood as how an individual interprets their life satisfaction based on their actual circumstances and the ideal standards prevailing in their environment. This study used qualitative methods, with participant selection using thepurposive sampling.The participants consisted of seven people, consisting of three single fathers and four single mothers with varying numbers of children, varying levels of education, aged under 60, having been single parents for more than a year, and not yet remarried. Single parent status included divorced and divorced. Data analysis used Interpretative Phenomenological Analysis (IPA) to explore the subjective meaning of participants' life experiences. The results indicate that the quality of life of single parents after divorce is influenced by emotional conditions, psychological challenges, coping strategies, social support, and gratitude practices. This research is expected to contribute to the development of psychology and serve as a reference to encourage single parents to improve their quality of life. Orang tua tunggal merupakan keadaan sepenuhnya ayah atau ibu saja bertanggungjawab atas keadaan keluarga setelah mengalami perceraian. Perubahan status dari berpasangan menjadi orang tua tunggal kerap menimbulkan dampak psikologis yang jika tidak tertangani dengan baik dapat menurunkan kualitas hidup. Kualitas hidup dipahami sebagai cara individu memaknai kepuasan hidupnya berdasarkan kondisi aktual yang ia jalani serta standar ideal yang berlaku dalam lingkungannya. Penelitian ini menggunakan metode kualitatif dengan penentuan partisipan menggunakan teknik purposive sampling. Partisipan berjumlah tujuh orang, terdiri dari tiga ayah tunggal dan empat ibu tunggal dengan jumlah anak bervariasi, tingkat pendidikan berbeda, berusia di bawah 60 tahun, telah menjadi orang tua tunggal lebih dari satu tahun, serta belum menikah kembali. Status orang tua tunggal mencakup cerai hidup dan cerai mati. Analisis data menggunakan Interpretative Phenomenological Analysis (IPA) untuk menggali makna subjektif pengalaman hidup partisipan. Hasil penelitian menunjukkan bahwa kualitas hidup orang tua tunggal setelah perceraian dipengaruhi oleh kondisi emosional, tantangan psikologis serta strategi bertahan, dukungan sosial, dan praktik rasa syukur dalam menjalani hidup. Penelitian ini diharapkan memberikan kontribusi terhadap pengembangan ilmu psikologi serta menjadi referensi yang mendorong orang tua tunggal untuk meningkatkan kualitas hidupnya.